Perjumpaan dengan Kristus melalui Hati Nurani bersama dengan Magisterium: Sebuah Studi Pemahaman Hati Nurani Orang Beriman yang Selaras dengan Ajaran Magisterium - Suwito, Benny (Institutum Theologicum Ioannis Mariae Vianney Surabayanum, 2020)
Encountering with Christ as Christians brings Christian acts as Christ’s acts because Christians’ acts are always act of faith. This cannot be separated from the role of conscience in human heart which relates to Magisterium. However, some Christians and theologians thought that Christians, in some of their human acts, do not need Magisterium because of the conscience in human heart that God has given show them to do good and avoid evil directly. Indeed, this opinion is not true. Christians always need Magisterium to act properly as the followers of Christ. Conscience is not individual truth but conscience is the voice of God which exists in human heart with Christian faith. Thus, Christians when they act something with their faith, they need Magisterium because knowing Christ is never knowing an idea of Christ but a personal faith experience to encounter with Christ. That’s why Christians have a relationship with Magisterium though conscience carries them to Jesus.